General Equilibrium Wage and Price Distributions - Albrecht, James W.; Axell, Bo; Lang, Harald (Quarterly Journal of Economics, 1986)
This paper extends models of search market equilibrium to incorporate general-equilibrium considerations. The model we treat is one with a single product market and a single labor market. An equilibrium distribution of prices and wages is the result of optimal price- and wage-setting behavior by firms in conjunction with optimal search by individuals. We prove the existence of a degenerate equilibrium and of a two-point dispersion equilibrium.